THE INFLUENCE OF WORK ACHIEVEMENT, EDUCATION, LOYALTY, AND HONESTY ON POSITION PROMOTION AT PT. SEGARA - Evi Sasmita; Faitullah Faitullah; Nurul Mardiyyah; Muhammad Furqon (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2023)
Promotion means moving from one position to another with a higher status and responsibility. That usually a move to a higher position is accompanied by an increase in salary or other wages, although this is not always the case. The factors that influence promotion in this research are work performance, education, loyalty and honesty. The purpose of this study was to determine the effect of work performance, education, loyalty, honesty partially and simultaneously on promotion at PT. SEGARA. this research is quantitative. The data collection instrument used a questionnaire. Sources of data used are primary data and secondary data. The results partially show that work performance (X1) has a significant effect on job promotion (Y), education (X2) has no significant effect on job promotion (Y), loyalty (X3) has no significant effect on job promotion (Y), honesty (X4) has a significant effect on promotion (Y). The results of the study simultaneously obtained F count of 11,395. Thus it can be concluded that F count > F table or (11.395 > 2.72) with a significant level of 0.000 because the significant level is <0.05, then H0 is rejected and Ha has been accepted meaning work performance (X1), education (X2), loyalty (X3) and honesty (X4) has a positive and significant effect simultaneously on the variable of promotion (Y) at PT. SEGARA. Recommendations or suggestions for further research using other factors outside of this research, namely skills, discipline, leadership, cooperation, and communicativeness.